Trabalhadores e confecções em Santa Helena-PR (décadas de 1980- 2000) - Silva, Rosane Marçal da (2016)
The topics developed in this thesis focuses on discussing and problematizing elements related to the growth process of the industrial production in the west of Paraná state, mainly Santa Helena in the period 1980 2000. This work provides an analytical inquiry of clothing industry workers background, so that to outline changes in their lives caused by this kind of industrial work. It tried to understand workers life and labor conditions and how class struggle they experience is built and articulated. As historical sources, this study relied on oral accounts from workers and industry owners, documents from local government and on press articles, above all those ones published by Costa Oeste newspaper.